2013
DOI: 10.1186/1756-6649-13-4
|View full text |Cite
|
Sign up to set email alerts
|

Real-time prostate motion assessment: image-guidance and the temporal dependence of intra-fraction motion

Abstract: BackgroundThe rapid adoption of image-guidance in prostate intensity-modulated radiotherapy (IMRT) results in longer treatment times, which may result in larger intrafraction motion, thereby negating the advantage of image-guidance. This study aims to qualify and quantify the contribution of image-guidance to the temporal dependence of intrafraction motion during prostate IMRT.MethodsOne-hundred and forty-three patients who underwent conventional IMRT (n=67) or intensity-modulated arc therapy (IMAT/RapidArc, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 27 publications
7
17
0
Order By: Relevance
“…There was a tendency for large IFPDs (≥3 mm) to increase with elapsed time. Our results were consistent with previous studies [1][2][3][4][5][6][7][8][9][10][11]. In our present study, an IFPD of ≥3 mm in each direction was detected in only ~2-3 % of all obtained TLS images (2,336 images).…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…There was a tendency for large IFPDs (≥3 mm) to increase with elapsed time. Our results were consistent with previous studies [1][2][3][4][5][6][7][8][9][10][11]. In our present study, an IFPD of ≥3 mm in each direction was detected in only ~2-3 % of all obtained TLS images (2,336 images).…”
Section: Discussionsupporting
confidence: 95%
“…To determine the optimal planning target volume (PTV) margins in non-realtime IGRT for prostate cancer, knowledge of intrafraction prostate displacement (IFPD) is necessary. Many previous studies, including non-real-time tracking studies and realtime tracking studies have pointed out the characteristics of IFPD as follows: (1) IFPD is larger in cranio-caudal (CC) and antero-posterior (AP) directions compared to the left-right (LR) direction [1][2][3][4][5][6][7][8][9][10][11], (2) individual differences in IFPD are significant [3][4][5]10], (3) IFPD increases with elapsed time in each fraction [6][7][8][9][10][11], and (4) large IFPDs are observed in a small proportion of all treatment time [1,[9][10][11]. Although these characteristics of IFPD have been clarified, institutional IFPD data should be assessed because significant differences in clinical practice may exist (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…As the EBRT time increases, the risk of significant intrafraction prostate motion increases. Cramer et al 9 evaluated intrafraction prostate motion during intensity modulated radiation therapy (IMRT) and volumetric modulated arc therapy (VMAT) using electromagnetic transponders and recommended patient repositioning when treatment duration exceeds 4 to 6 minutes. Shelton et al 10 observed a similar relationship between treatment duration and intrafraction prostate motion, with shorter treatment times achieved with VMAT (compared with IMRT), which resulted in a 30% to 40% reduction in intrafraction prostate motion.…”
Section: Rt Fractionation Definitionsmentioning
confidence: 99%
“…The pattern of an individual patient is unpredictable and any of the six motion patterns can occur during each fraction. In any case, the positional uncertainty increases with time [12][13][14][15][16]. The increased dose per fraction and thereby increased treatment time for hypofractionation could lead to larger positional uncertainty due to the prostate motion.…”
Section: Introductionmentioning
confidence: 99%